Analyzing the Significance of Reformed Epistemology: A Critical Review of Criticism of Evidentialism and its Implications for Evangelical Apologetics - Kristiani Yanti Kana; Delf Gustaf Kalalo (Indonesian Journal of Christian Education and Theology, 2026)
Reformed Epistemology (RE) is one of the most significant developments in the philosophy of religion of the 20th and 21st centuries. This article analyzes the significance of Reformed Epistemology, focusing on its critique of evidentialism and its implications for the practice of evangelical apologetics. Through a critical literature review approach, this paper will outline the core arguments of Reformed Epistemology, particularly the thesis of "properly basic belief" in religious faith. The analysis will focus on the perspective of John D. Laing, who examines the triangular relationship between Reformed Epistemology, evidentialism, and apologetics. The article's findings demonstrate that Reformed Epistemology's significance lies in its ability to provide a legitimate epistemic foundation for religious belief without relying on propositional evidence, while simultaneously opening up space for a model of apologetics that is more testimonial and relies on the work of the Holy Spirit, rather than solely rationalistic. However, Reformed Epistemology has also drawn criticism for its potential fideism and its challenges to interfaith dialogue.